Digital single market and territoriality of copyright - de Miguel Asensio, Pedro Alberto (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
A distinctive feature of the EU is the particularly high level of harmonisation of the national copyright regimes. This may facilitate the adoption of specific mechanisms to get around the current fragmentation within the internal market in the absence of a single EU copyright title. Enforcement measures based on national rights are limited to the territory of the respective rights, although the possibility to adopt measures with respect to the Union or several Member States depends, first of all, on the extent of the jurisdiction granted to national courts. A renewed trend to have recourse to the country of origin principle to overcome some of the obstacles posed to the digital single market by the national copyright regimes can be found in some recent instruments. Regulation (UE) 2017/1128 and Directives (EU) 2019/789 and 2019/790 are discussed with a particular focus on their impact on cross-border activities.
Keywords: copyright and related rights; European Unión; Internet; jurisdiction; choice of law